THE INFLUENCE OF PROMOTIONAL COSTS, SALES VOLUME, OPERATIONAL EXPENSES AND PRODUCTION COSTS ON NET PROFIT IN THE FOOD AND BEVERAGE SUB SECTORS LISTED ON THE INDONESIAN STOCK EXCHANGE IN THE PERIOD 2018–2022 - ,; ,; ,; , (Bilancia : Jurnal Ilmiah Akuntansi; Vol 9 No 1 (2025): Bilancia : Jurnal Ilmiah AkuntansiDO - 10.35145/bilancia.v9i1.4857, 2025)
This research aims to determine the influence of Promotion Costs, Sales Volume, Operational expenses and Production Costs on the Net Profit of the food and beverage subsector listed on the IDX for the 2018-2022 period. This research uses secondary data. The sampling technique in this research used purposive sampling. The number of samples obtained was 23 companies. This research analysis method uses descriptive analysis and several types of evaluation using the help of SmartPLS software. The results of this research indicate that promotional costs do not have a significant effect on net profit. Sales volume does not have a significant effect on net profit. Operational expenses have a significant effect on net profit. Production costs do not have a significant effect on net profit. Penelitian ini bertujuan untuk mengetahui pengaruh Biaya Promosi, Volume Penjualan, Biaya Operasional dan Biaya Produksi terhadap Laba Bersih subsektor makanan dan minuman yang terdaftar di BEI periode 2018-2022. Penelitian ini menggunakan data sekunder. Teknik pengambilan sampel dalam penelitian ini menggunakan purposive sampling. Jumlah sampel yang diperoleh sebanyak 23 perusahaan. Metode analisis penelitian ini menggunakan analisis deskriptif dan beberapa jenis evaluasi dengan menggunakan bantuan software SmartPLS. Hasil penelitian ini menunjukkan bahwa biaya promosi tidak berpengaruh signifikan terhadap laba bersih. Volume penjualan tidak berpengaruh signifikan terhadap laba bersih. Biaya operasional berpengaruh signifikan terhadap laba bersih. Biaya produksi tidak berpengaruh signifikan terhadap laba bersih.